Du rôle des affaires dans la politique canadienne d'aide au développement : le cas des télécommunications - Martinez, Andréa (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
This article focuses on the reorientation of the Canadian development assistance policy during the 1980's to foster the emergence of a North-South partnership in which the business community would be a key actor. It is questionable whether the funding levels and geographical priorities of telecommunication projects undertaken by the Canadian private sector through CIDA'S Industrial Cooperation Program may lead to such a partnership. Sectorial allocations, albeit still sparse, reveal a selective marginalization of Third World Economies, as they are concentrated on a few Latin American and Asian middle-income countries.